The framework of safety management on university laboratory. (December 2022) - Yang, Jianfeng; Xuan, Shenqing; Hu, Yuanhao; Liu, Xinyong; Bian, Mingcheng; Chen, Liangchao; Lv, Siyun; Wang, Pengchao; Li, Ru; Zhang, Jianwen; Shu, Chi-Min; Dou, Zhan
Abstract: In recent years, with accidents in campus laboratories happening more frequently, and sporadically many personnel and property concerned are under serious threat. To address this issue, it has become a priority for universities in China to enhance safety management in the laboratory. To begin with, this study analyzed accidents that occurred in a university laboratory in the past ten years. The aim of this act was to conclude the problems in current safety management in the university laboratory. This was followed by exploring solutions and measures for those problems, making hazardous chemicals management a critical factor in campus laboratory safety management. With this idea, an assessment of hazardous chemicals of their holistic life-cycle on campus has been conducted, which realizes the information perception throughout its entire life-cycle on campus as well. Last but not least, a platform for safety and emergency management of hazardous chemicals has been built. This platform can act as a catalyst, effectively improving the regulatory levels of hazardous chemicals. Thus, the main responsibility for hazardous chemicals units can be further implemented. Through the construction of the safety management system for the full life-cycle of hazardous chemicals, the process of safety management of the university laboratory is fulfilled, and the inherent safety of the university laboratory is finally realized. Highlights: Information perception for hazardous chemicals life-cycle in universities is analyzed. The safety emergency management platform of hazardous chemicals in universities has been built. The process safety management (PSM) is applied to the safety management of university laboratory.